Material Ergonomics on Application of Wooden Floors in the Interior of the Workspace Office - Tunjung Atmadi; Ika Yuni Purnama (Pascasarjana Institut Seni Indonesia Surakarta, 2021)
Workspace from an office interior and requires serious management related to its use. This research aims to use space-forming elements in the workspace’s interior design using wood flooring as parquet. The focus is on the choice of wood use concerning the elements in its application. This research rests on the assumption that wood material choice for the workspace floor has met safety, comfort, and beauty requirements. The hope is that with these three conditions’ fulfillment, the office's activities can run smoothly, safely, and pleasantly. The method used in this research is a descriptive qualitative method. An approach puts forward a description based on field observations and documentation to describe the research object’s situation. This study aims to reveal aesthetic, comfort, and safety studies of wooden floors in the workspace interior with their advantages and disadvantages.